A genealogy of the private military and security companies: the trajectory of DynCorp towards the formation of the “market for force” in the United States (Tempo e Argumento, 2021)
Private military and security companies (PMSC) are an emerging actor in debates about contemporary conflicts, mainly because of their large participation alongside US troops in the Afghanistan and Iraq Wars. The literature on the subject in general reacted to the emergence and growth of the so-called “market for force”, identifying what would be a moment of genesis of these companies, the end of the Cold War or the post-9/11 period. Despite this, throughout the twentieth century it is possible to identify in the United States a set of transformations in military procedures, in technologies, in the norms that regulated outsourcing and in the private actors’ behavior that shaped the current state of the market for private military services and that made the explosion of this phenomenon possible since the 1990s. The option for a genealogy, produced through the reconstitution of the development of DynCorp, from its origins in the post-World War II until its participation in the Iraq War, seeks to indicate that the current PMSC market emerges from long-term adaptations of companies and their main client, the US government. The association between the PMSC and other actors and economic sectors indicates an economic dimension of contemporary conflicts related not only to their ends, but also to the means at hand.